Condom-Associated Erection Problems: A Study of High-Risk Young Black Males Residing in the Southern United States. (March 2016) - Graham, Cynthia A.; Crosby, Richard; Sanders, Stephanie; Milhausen, Robin; Yarber, William L.
Previous research indicates that young men may experience condom-associated erection loss and that these problems may lead to inconsistent or incomplete condom use. The primary aim of this study was to assess, using a retrospective recall period of 2 months, correlates of condom-associated erection problems among young Black men attending sexually transmitted infection (STI) clinics. Data were collected in clinics treating patients with STIs in three southern U.S. cities. Males 15 to 23 years of age who identified as Black/African American and reported recent (past 2 months) condom use were eligible. A total of 494 men participated. Nineteen percent reported that condom-associated erection problems during condom application occurred at least once, and 17.8% indicated erection difficulties occurred during sexual intercourse at least once in the past 2 months. Multivariate analyses identified that condom-associated erection problems were associated with reports of sex with more than one partner during the recall period, reported problems with condom fit and feel, lower motivation to use condoms, and attempts at condom application before having a full erection. Findings suggest that clinic interventions should address possible condom-associated erection problems among young Black men who are at risk of STIs. Encouraging men who may be vulnerable to erection loss when condoms are used to allow sufficient time for sexual arousal to build may be an effective strategy.